Study on static and fatigue strength of structural adhesive-bonded joints of steel sheets for automotive application. Issue 5 (4th May 2018) - Fujimoto, Hiroki; Ueda, Hideki; Imamura, Takashi; Ueji, Rintaro; Fujii, Hidetoshi
ABSTRACT: The static and fatigue strength of crush durable structural adhesive-bonded lap joints of steel sheets for automobiles was evaluated by tensile shear tests. The steel sheets used in this study were uncoated and galvannealed (GA) with tensile strength ranging from 270 MPa-grade to 980 MPa-grade and the thickness ranging from 0.7 to 1.8 mm. Also, the effects of the adhesive types were evaluated. The results are as follows: In the static tensile shear tests, when the steel sheets deformed during the tensile test, the tensile shear strength increased with the increase in the base metal properties, such as the yield strength and thickness; however, when the base metal properties were sufficiently high not to undergo plastic deformation, the tensile shear strength exhibited a constant value. On the other hand, the effect of base metal properties on the fatigue joint strength was relatively small. The static joint strength of the GA steel joints was slightly lower than that of the uncoated steel sheets; however, the fatigue strength of the GA steel joints was higher than that of the uncoated steel sheets. The coating failure of the GA was affected by the type of adhesive, base metal properties and type of test. Choosing the proper adhesive can reduce the failure of the GA coating, and the high strength steel showed fewer coating failures than the mild steel.